PREPARATION OF MESOPOROUS TITANIA-SILICA AEROGELS BY CO2 SUPERCRITICAL EXTRACTION - Silvester Tursiloadi; Dinie Mansur; Yeny Meliana; Ruslan Efendi (Universitas Gadjah Mada, 2007)
Stable anatase is attractive because of its notable functions for photocatalysis and photon-electron transfer. TiO2-nanoparticles dispersed SiO2 wet gels were prepared by hydrolysis of Ti(OC4H9n)4 and Si(OC2H5)4 in a 2-propanol solution with acid catalyst. The solvent in the wet gels was supercritically extracted using CO2 at 60 oC and 22 Mpa in one-step. Thermal evolution of the microstructure of the extracted gels (aerogels) was evaluated by XRD measurements, TEM and N2 adsorption measurements. The as-extracted aerogel with a large specific surface area, more than 365 m2g-1, contained anatase nanoparticles, about 5 nm in diameter. The anatase phase was stable after calcinations at temperatures up to 1000 oC, and BET specific surface area, total pore volume and average pore diameter did not change significantly after calcinations at temperature up to 800 oC.